Quantitative risk-based approach for improving water quality management in mining - Liu, W.; Moran, Chris; Vink, S. (American Chemical Society, 2011)
The potential environmental threats posed by freshwater withdrawal and mine water discharge are some of the main drivers for the mining industry to improve water management. The use of multiple sources of water supply and introducing water reuse into the mine site water system have been part of the operating philosophies employed by the mining industry to realize these improvements. However, a barrier to implementation of such good water management practices is concomitant water quality variation and the resulting impacts on the efficiency of mineral separation processes, and an increased environmental consequence of noncompliant discharge events. There is an increasing appreciation that conservative water management practices, production efficiency, and environmental consequences are intimately linked through the site water system. It is therefore essential to consider water management decisions and their impacts as an integrated system as opposed to dealing with each impact separately. This paper proposes an approach that could assist mine sites to manage water quality issues in a systematic manner at the system level. This approach can quantitatively forecast the risk related with water quality and evaluate the effectiveness of management strategies in mitigating the risk by quantifying implications for production and hence economic viability. © 2011 American Chemical Society.